Laparoscopic-assisted Gastrectomy for Gastric Cancer with D2 Lymphadenectomy: Experience with more than 500 Cases at Military Hospital, Vietnam - Ho Chi Thanh; Hoang Manh An; Dang Viet Dung; Nguyen Trong Hoe; Tran Doanh Hieu; Nguyen Van Tiep; Lai Ba Thanh; Le Thanh Son (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Among the less invasive operations noted in recent years, laparoscopic gastrectomy (LG) for gastric cancer has become popular because of advances in surgical techniques. We have performed LG with D2 lymphadenectomy for 515 cases of gastric cancer between April 2009 and November 2019 at military hospital 103. AIM: We aimed to presented the techniques and results of laparoscopic-assisted gastrectomy (LAG) for gastric cancer. METHODS: Of the 515 gastric malignancy cases, distal gastrectomy was performed in 402 cases, proximal gastrectomy in 37 cases, and total gastrectomy in 76 cases. In all the cases, D2 lymph node dissection was performed according to the general rule of the Japanese gastric cancer association 3rd. RESULTS: Quicker recovery was observed in the LG cases than in the open cases. The post-operative complications with this technique were within a permissible range. There was a statistical difference that was seen in the survival outcomes after LAG for gastric cancer between the laparoscopic-assisted distant, proximal, and total gastrectomy. CONCLUSION: The laparoscopic technique is not only less invasive but also relatively safe and curative compared with open gastrectomy for advanced gastric cancer.